A carbon-nanotube based nano-furnace for in-situ restructuring of a magnetoelectric oxide - Bajpai, Ashna; Klingeler, Rüdiger (Carbon, 2017)
We present current-voltage (I-V) characteristics of an individual carbon nanotube (CNT) filled with Cr2O3, a multi-functional magnetic oxide relevant to spintronics. We demonstrate that a filled CNT during a two probe I-V scan in suspended geometry, can be used like a nano-furnace for controlled restructuring of the oxide encapsulate. With proper utilization of Joule heating during I-V scans, the encapsulate, initially in the form of a polycrystalline nano-wire, converts to beads, nano-crystals and sheets within the CNT. These morphological phases are formed and preserved by controlling the amplitude, rate and holding time of the bias voltage. The sequential restructuring, observed in real time by Transmission Electron Microscopy (TEM), is also accompanied by a substantial enhancement in the current flowing through the CNT. We further demonstrate that advantageously tailoring the morphology of the encapsulate is linked to this current enhancement and can be a route for heat dissipation in nano devices. Magnetization measurements reveal that Cr2O3, a well known antiferromagnetic and magnetoelectric, when confined within CNT, exhibits logarithmic time dependence. This slow magnetization dynamics is associated to a pinning mechanism that points towards the possibility of stress induced moments in this system. These measurements elucidate novel magnetic properties of the encapsulate.